Superior real‐time polymerase chain reaction detection of Babesia microti parasites in whole blood utilizing high‐copy BMN antigens as amplification targets. Issue 8 (17th April 2018) - Grabias, Bryan; Clement, Jean; Krause, Peter J.; Lepore, Timothy; Kumar, Sanjai
Abstract : BACKGROUND: Babesiosis is a zoonotic disease transmitted to humans by the bite of infected ticks and caused by apicomplexan parasites, most commonly Babesia microti . Additionally, blood and blood products collected from asymptomatically infected blood donors may cause transfusion‐transmitted infections in recipients. Highly sensitive molecular assays that detect parasite nucleic acid are needed for laboratory diagnosis and to identify and defer clinically silent but parasitemic blood donors. STUDY DESIGN AND METHODS: Here we report the development and analytical and clinical characterization of a real‐time polymerase chain reaction (RT‐PCR)–based assay for the detection of B. microti genomic DNA in whole blood. We evaluate the detection of Babesia parasites using two separate targets, the traditional18S ribosomal subunit gene ( Bm 18S) and members of the abundant BMN family of seroreactive antigens ( Bm BMN). RESULTS: Analytical sensitivity determination using a probit analysis demonstrated an analytical sensitivity of 30.9 parasites/mL for 18S amplification and 10.0 parasites/mL for BMN amplification The BMN primer set also demonstrates superior sensitivity for serial dilution panels prepared from clinically diagnosed Babesia ‐infected blood samples, generally detecting 10‐fold more dilute nucleic acid. CONCLUSIONS: Cumulatively, our data demonstrate that RT‐PCR detection of the BMN family of seroreactive antigens reflects a sensitive and superior assay for the detection of B. microti in whole blood samples.